Facility Layout Redesign for an SME Printing Industry Using Systematic Layout Planning: A Case Study in Dumai - Dwi Julianti; Fitra Fitra; Muhammad Haikal; Rona Uli Sitinjak (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The printing SME sector often encounters inefficient facility layouts, leading to extended material flow, low productivity, and increased operational costs. This study aims to redesign the facility layout of Jasatama Computer SME in Dumai City to enhance spatial efficiency and workflow. The methods applied are Systematic Layout Planning (SLP) and a graph-based approach, using the rectilinear distance, activity relationship chart, and from-to chart to map the interrelationships among workstations. The practical implications of this study include improved spatial utilization, smoother material flow, and potential enhancement of productivity and workplace ergonomics in printing SME. From a scientific perspective, this research contributes by providing a comparative analysis of two layout design methods, SLP and the graph-based approach, in the SME printing sector, which has been rarely explored in prior studies. The findings highlight that adopting quantitative and systematic methods in facility layout redesign can be an effective solution to support SME sustainability and competitiveness. The analysis results indicate that the initial layout generated a total material transfer distance of 205.85 meters. The proposed SLP-based layout reduced the distance to 168.43 meters, while the graph-based approach produced 180.91 meters. Consequently, the SLP method achieved an 18.16% reduction in material handling distance, making it a more optimal alternative compared to the other method.